PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT. RAJAWALI NUSINDO CAB. MEDAN - Resnita Mersalina Simbolon; Nurul Wardani (Universitas Negeri Medan, 2015)
Human resources or employee is the main driver of the success of a company that needs special attention from the company so that employees can work more diligently in order to achieve company goals. The purpose of this study was to determine the effect of leadership and motivation on employee performance at PT. Rajawali Nusindo Medan Branch. The study population was all employees at PT. Rajawali Nusindo Medan Branch karyawanya number reached 73 (seventy-three). The samples used total sampling so that the sample drawn from the entire population. The data used in this study are primary data obtained through questionnaires in the study sample, amounting to 73 respondents. The test used is the quality of the test data and test the classical assumptions. Hypothesis testing is done by multiple regression analysis, simultaneous F test and the partial test. The result showed that simultaneous leadership and motivational variables affect the performance of employees at PT. Rajawali Nusindo Medan Branch, where the F count> F table or 16.196 > 3.128 with a level of significant (α) 0,000 < 0,005. The coefficient of determination (adjusted R square) of 0.316 means that the influence of leadership and motivation on the performance of employees of PT. Rajawali Nusindo Medan Branch 31.6% and the remaining 68.4% is influenced by other variables outside of research. Conclusions from the research that there is a positive and significant effect of leadership and motivation on employee performance at PT. Rajawali Nusindo Medan Branch. It is expected that the people at the at PT. Rajawali Nusindo Medan Branch further enhance the leadership and motivation so that employees work even harder to compete and will automatically improve its performance in the company. Keywords: Leadership, Motivation, Performance